ANALISIS KESALAHAN SISWA DALAM MENYELESAIKAN SOAL MATEMATIKA PADA MATERI OPERASI BENTUK ALJABAR DI KELAS VII SMP KATOLIK SANTA ROSA DE LIMA TONDANO - Runtu, Patricia; Regar, Vivian; Rengkuan, Cikita (Universitas Negeri Manado, 2020)
ABSTRACT. This study was conducted to describe type of errors done by students and find out the factors causing those errors. This qualitative descriptive research, involving nineteen 7th graders students at SMP Katolik Santa Rosa de Lima Tondano as research subjects. The test and interview were used as data collection technique. Based on the result of data identification, it is concluded that: (1) There were no students doing errors in comprehending algebra operation questions (2) 24,69% of students made errors on the kind of algebra basic form (3) 19,75% of students made errors in solution procedure, and (4) 43,21 of students made errors on the kind of calculations. The interview resulted in that the most type of errors conducted by students was the operation of algebra forms, summation of negative numbers, variable concept and the like terms. Key Words: Analysis of Student Errors, Mathematics Solving, Operation of Algebra.